Symptomatic Heterotopic Bone Formation after 1,2 ICSRA in Scaphoid Nonunions - Ghijsen, S. C.; Heeg, E.; Teunis, T.; den Hollander, V. E. C.; Schuurman, A. H. (Journal of Wrist Surgery, 2023)
Background We observed several cases of heterotopic bone formation after a 1,2 intercompartmental supraretinacular artery (1,2 ICSRA) distal radius vascularized bone graft (VBG) for the treatment of scaphoid nonunion. This adverse event seems underreported. Knowledge about factors associated with the formation of heterotopic bone after VBGs might help reduce this adverse event.Purpose What factors are associated with resected heterotopic bone formation after 1,2 ICSRA distal radius graft for the treatment of scaphoid nonunion?Patients and Methods We retrospectively reviewed all patients with a scaphoid nonunion treated with a 1,2 ICSRA distal radius graft between 2008 and 2019 in an urban level 1 trauma center in the Netherlands. We included 42 scaphoid nonunions in 41 people treated with the 1,2 ICSRA graft. We assessed potential correlation with patient, fracture, and treatment demographics.Results Heterotopic bone developed in 23 VBGs (55% [23/42]), of which 5 (12% [5/42]) were resected. Heterotopic bone was located radially (at the pedicle side) in all participants. Except a longer follow-up time (p = 0.028), we found no variables associated with the development of heterotopic bone formation.Conclusion The location of the heterotopic bone at the pedicle site in all cases suggests a potential association with the periosteal strip. Surgeons might consider not to oversize the periosteal strip as a potential method to prevent heterotopic ossification after VBG.Level of Evidence Level II, prognostic study.
Keywords: heterotopic bone formation; scaphoid nonunion; 1, 2 ICSRA distal radius graft; vascularized bone graft